Sociocultural determinants of place of birth among Sudanese women - Abdulmageed, Samia S.; Elnimeri, Mustafa K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternal health has been accounted as challenge to the public health policy makers around the globe, which has more commonly been threaten by the cultural and social forces. The aim of this study was to investigate the sociocultural determinants of health-seeking behavior of Sudanese women from Sharq-Alneel Locality regarding the place of delivery. Methods: A cross-sectional community based study was conducted from June 2017- January 2018 using face-to-face structured questionnaire to 576 Sudanese women age of 15-49 years from 4 Administrative Units. A multistage cluster sampling technique was adopted. Binary and multinomial logistic regression models were used to analyse the results. Results: Rural women respondents were 329 (57%). A 147 (28.3%) of the studied population gave birth at home at least once. A 110 (20.8%) women respondents preferred delivery at home. Of those home deliveries, complications occurred to 42 (26.9%) compared to the one occurred to women 114 (73.1%) who delivered in health facility. Circumcision among respondents was 80.7% and had insignificant association with complications occurred during delivery. Multinomial analysis showed women with no education were 33.5 times more likely (O.R=33.5, CI=9.8-114.0, p<0.001), primary education (O.R=6.4, CI=2.7-15.2, p<0.001), secondary (O.R=4.9, CI=2.1-11.5, p<0.001) to seek home delivery compared to those who obtained university education. Financial reasons for delivering at home were were 11.5 (O.R=11.5, CI=2.5-53.7, P=0.002) times, while nearby (distance to health facility) as a reason for delivering at home were 3.7 (O.R=3.7, CI=1.1-13.0, P=0.04) times more likely relative to those who reported staff competency as a reason for delivering at health facility. Conclusions: Age, residence area, number of children, education, financial income, distance to health facility, and source of decision for women’s place of delivery were significant determinants of deliveries at home. Special attention is needed at community level for health education towards culture and believes affecting women’s decision on delivery at home. To promote reproductive health of women and improve quality of care giving by health personnel.